Penerapan Model Konseling Kristen Solution-Based Brief Therapy Counseling Terhadap Remaja yang Mengalami Bullying - Fanny Selviani; Gery Altobely Seroh; Agus Nugroho (STT INTI Bandung, 2023)
Bullying is a behavior that occurs when someone often oppresses someone physically, verbally or relationally. This causes someone to experience the impact of bullying. This research aims to determine the description experienced by victims of bullying. The method used in this research is a descriptive qualitative method and collects data through interviews and observation. The respondents studied were teenagers who experienced bullying. From the results of the interview, it was found that the impact experienced had a bad effect, namely a feeling of trauma and fear of other people due to the treatment of friends in the school environment. This impact is in the form of the informant preferring to remain silent and being treated no matter what and being overshadowed by past events so that he/she becomes a more closed person. For this reason, the author raised the title